2015
DOI: 10.1007/s11205-015-1154-8
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Contribution of Trade Openness and Foreign Direct Investment in Life Expectancy: The Long-Run and Short-Run Analysis in Pakistan

Abstract: This paper examines the impact of trade openness and foreign direct investment (FDI) on life expectancy using time series data over the period of 1972-2013. We have applied structural break unit root as well as cointegration tests to examine integrating properties of the variables and cointegration among the variables. The causal linkage between the variables has been tested by applying the VECM Granger causality. The empirical evidence confirms the presence of cointegration amid the variables. Moreover, trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 45 publications
11
62
0
Order By: Relevance
“…Across studies, the same indicators were used to represent different constructs. Total trade relative to GDP was used as a measure of trade openness [ 45 , 50 ], trade liberalization [ 29 , 47 ], and economic globalization [ 51 ]; FDI was used as a measure of globalization [ 46 ] and “market integration” [ 52 ]. The various globalization and macroeconomic indices conflate trade and investment, precluding any disentanglement of these effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across studies, the same indicators were used to represent different constructs. Total trade relative to GDP was used as a measure of trade openness [ 45 , 50 ], trade liberalization [ 29 , 47 ], and economic globalization [ 51 ]; FDI was used as a measure of globalization [ 46 ] and “market integration” [ 52 ]. The various globalization and macroeconomic indices conflate trade and investment, precluding any disentanglement of these effects.…”
Section: Resultsmentioning
confidence: 99%
“…The various globalization and macroeconomic indices conflate trade and investment, precluding any disentanglement of these effects. Only four studies considered both trade and investment as separate explanatory indicators [ 20 , 23 , 24 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because recent studies have found that international integration improves health outcomes (Alam, Raza, Shahbaz, & Abbas, ; Burns, Jones, Goryakin, & Suhrcke, ; Herzer, ; Majeed, ), we include the sum of trade and FDI as a share of GDP to assess the link between integration and life expectancy. In line with Nagel, Herzer, and Nunnenkamp (), we find that the relationship between global integration and health is inconclusive (Column 3).…”
Section: Robustness Testsmentioning
confidence: 99%
“…For this purpose, we check the stability of the coefficients governing the long-run relationship by using the rolling window estimation method with the window size of 10 years (M. S. Alam, Raza, Shahbaz, & Abbas, 2015;Raza, Shahbaz, & Paramati, 2016). Figure 3 and Table 11 report the evolution of the coefficients associated with GDP, population, energy consumption and urbanization throughout the sample.…”
Section: Stability Of Long Run Modelmentioning
confidence: 99%